2017
DOI: 10.1088/1361-665x/aa6387
|View full text |Cite
|
Sign up to set email alerts
|

Tuning sound with soft dielectrics

Abstract: Soft dielectric tubes undergo large deformations when subjected to radial voltage. Using the theory of nonlinear electroelasticity, we investigate how voltage-controlled deformations of these tubes in an array alter acoustic wave propagation through it. We show that the propagation is annihilated across a certain audible frequency range, referred to as a sonic band gap. We carry out a numerical study, to find that the band gap depends nonlinearly on the voltage, owing to geometrical and material nonlinearities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…On the other hand, auxetic materials present very interesting features 17 – 21 originating from negative Poisson’s ratio, such as increased shear modulus, indentation resistance, fracture toughness, energy absorption, porosity/permeability variation with strain and synclastic curvature, which also depend on the topology of the unit cell. It is therefore very interesting to study the combination of such properties 22 25 to obtain a metamaterial endowed with controllable phononic bandgaps 26 , 27 to be tailored, degraded or enhanced during its functioning. Several tunable PnCs, 28 , 29 which take advantage of different materials or properties combined together, are available.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, auxetic materials present very interesting features 17 – 21 originating from negative Poisson’s ratio, such as increased shear modulus, indentation resistance, fracture toughness, energy absorption, porosity/permeability variation with strain and synclastic curvature, which also depend on the topology of the unit cell. It is therefore very interesting to study the combination of such properties 22 25 to obtain a metamaterial endowed with controllable phononic bandgaps 26 , 27 to be tailored, degraded or enhanced during its functioning. Several tunable PnCs, 28 , 29 which take advantage of different materials or properties combined together, are available.…”
Section: Introductionmentioning
confidence: 99%
“…where Most of the existing researches on soft DE PCs take no account of material compressibility [29][30][31][32][33][34].…”
Section: Nonlinear Deformation Of a Homogeneous De Cylindermentioning
confidence: 99%
“…Shmuel and Pernas-Salomón [31] proposed an effective way to realize mode localization in DE films via electrostatically controlled aperiodicity. Noticing that the analysis in Yang and Chen [24] is not fully nonlinear, Bortot and Shmuel [32] performed a re-examination and found that the snap-through instability resulting from geometrical and material nonlinearities can be harnessed to achieve sharp transitions in the acoustic BG. Galich and Rudykh [33] re-examined the problem that was studied by Shmuel and deBotton [30] and arrived at a different conclusion that shear waves propagating perpendicular to the layers in ideal neo-Hookean DE laminates are not affected by the electric field directly.…”
Section: Introductionmentioning
confidence: 99%
“…The snap-through instability of SEA balloons was used by Rudykh et al (2012) to design electrostatically controllable actuators and micropumps. Recently, the snap-through instability of phononic crystals made of SEA cylindrical structures was also utilized to realize sharp transitions in the bandgap width and position (Bortot and Shmuel, 2017;Wu et al, 2018c). As a result, another goal of this paper is focused on how the resonant frequency of a SEA spherical balloon is influenced by the phenonenon of snap-through instability.…”
Section: Introductionmentioning
confidence: 99%